2020
DOI: 10.1038/s41368-019-0069-7
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory cytokine TNFα promotes HPV-associated oral carcinogenesis by increasing cancer stemness

Abstract: High-risk human papillomaviruses (HPVs) are involved in the development of several human cancers, including oropharyngeal squamous cell carcinomas. However, many studies have demonstrated that HPV alone is not sufficient for the oncogenic transformation of normal human epithelial cells, indicating that additional cofactors are required for the oncogenic conversion of HPV-infected cells. Inasmuch as chronic inflammation is also closely associated with carcinogenesis, we investigated the effect of chronic exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…A recent study showed that exposure to chronic inflammation induced by TNF-α contributes to the persistence of HPV-infected keratinocytes and their transformation into immortalized cells with greater mutagenic potential. It has been suggested that HPV alone is insufficient for oncogenic conversion and that TNF-α acts as a cofactor for this transformation (Hong et al, 2020). Therefore, it is assumed that blockade of TNF-α with immunobiologicals can play a protective role against malignancies involving HPV.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that exposure to chronic inflammation induced by TNF-α contributes to the persistence of HPV-infected keratinocytes and their transformation into immortalized cells with greater mutagenic potential. It has been suggested that HPV alone is insufficient for oncogenic conversion and that TNF-α acts as a cofactor for this transformation (Hong et al, 2020). Therefore, it is assumed that blockade of TNF-α with immunobiologicals can play a protective role against malignancies involving HPV.…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that IL-1β can increase the formation of colon cancer spheres, which show an up-regulation of stemness factor genes and increased drug resistance [ 134 ]. Finally, tumor necrosis factor (TNF)-α promotes HPV-associated oral carcinogenesis by increasing stemness [ 135 ].…”
Section: Influence Of the Microenvironment On Cscmentioning
confidence: 99%
“…Despite targeted therapeutic approaches in the treatment of chronic myeloid leukemia (CML), BCR-ABL-independent mechanisms seem to exist which sustain the survival of leukemic stem cells (LSCs) as minimal residual disease or persister cells with increased stem cell characteristics and quiescence [60] . Chronic inflammation and tumor necrosis factor α (TNFα), the major proinflammatory cytokine was found to induce malignant growth and stemness phenotype in HPV-infected oral cancer cells [61] . TIC population in pancreatic ductal adenocarcinoma (PDAC) was marked by high cell surface levels of the tetraspanin CD9 correlated with poorer survival, showed pronounced epithelial and mesenchymal cancer cell populations, re-initiated tumor formation and recapitulated the cellular heterogeneity of primary PDAC.…”
Section: Cancer Stem Cells Emt and Metastasismentioning
confidence: 99%